Mapping UK mental health services for adults with attention-deficit/hyperactivity disorder: national survey with comparison of reporting between three stakeholder groups. Issue 4 (July 2020) - Price, Anna; Janssens, Astrid; Newlove-Delgado, Tamsin; Eke, Helen; Paul, Moli; Sayal, Kapil; Hollis, Chris; Ani, Cornelius; Young, Susan; Dunn-Morua, Susan; Asherson, Philip; Logan, Stuart; et al.
Abstract : Background: UK clinical guidelines recommend treatment of attention-deficit hyperactivity disorder (ADHD) in adults by suitably qualified clinical teams. However, young people with ADHD attempting the transition from children's to adults' services experience considerable difficulties in accessing care. Aims: To map the mental health services in the UK for adults who have ADHD and compare the reports of key stakeholders (people with ADHD and their carers, health workers, service commissioners). Method: A survey about the existence and extent of service provision for adults with ADHD was distributed online and via national organisations (e.g. Royal College of Psychiatrists, the ADHD Foundation). Freedom of information requests were sent to commissioners. Descriptive analysis was used to compare reports from the different stakeholders. Results: A total of 294 unique services were identified by 2686 respondents. Of these, 44 (15%) were dedicated adult ADHD services and 99 (34%) were generic adult mental health services. Only 12 dedicated services (27%) provided the full range of treatments recommended by the National Institute for Health and Care Excellence. Only half of the dedicated services (55%) and a minority of other services (7%) were reported by all stakeholder groups ( P < 0.001, Fisher's exact test). Conclusions: There is geographical variation in the provision of NHS services for adults with ADHD across the UK, as well as limited availability of treatments in the available services. Differences between stakeholder reports raise questions about equitable access. With increasing numbers of young people with ADHD graduating from children's services, developing evidence-based accessible models of care for adults with ADHD remains an urgent policy and commissioning priority.